Exploring Teachers’ Digital Readiness in Rural Indonesia: A Case Study of Infrastructure and Technology Access in a 3T Area - Citra citra; Karimuddin Karimuddin; Syarif Hidayat Nasir; Roslina Roslina; Susi Astianti (FOSTER: Journal of English Language Teaching, 2026)
This study explores teachers’ professional digital readiness in facing digital transformation by examining access to infrastructure and technology in a rural senior high school located in a 3T area of Indonesia. Using a qualitative case study design, this research involved seven teachers from a public senior high school in East Kolaka Regency, Southeast Sulawesi. Data were collected through semi-structured interviews and analyzed using thematic analysis to capture teachers’ experiences, challenges, and institutional conditions related to digital learning implementation. The findings indicate that teachers generally possess basic digital literacy and positive attitudes toward technology use. However, digital practices remain limited to fundamental tools and are not yet pedagogically integrated. Teacher digital readiness is influenced by internal factors, such as motivation, confidence, and prior experience, as well as external factors, including limited device availability, unstable internet connectivity, insufficient professional development, and unequal student access to technology. The study further demonstrates that inadequate infrastructure constrains the translation of teacher readiness into sustained digital practice. This study contributes a micro-level and contextualized understanding of teacher digital readiness in rural 3T contexts, highlighting the interplay between individual, institutional, and infrastructural factors, and offers implications for developing more inclusive and context-responsive digital education policies.